Homocysteine Is a Risk Factor in Predialysis Patients When Associated with Malnutrition and Inflammation. (26th May 2010) - Vieira, Ana de Lurdes Agostinho Cabrita; Baptista, Alexandre; Malho, Anabela; Pinho, Ana; Silva, Ana Paula; Bernardo, Idalécio; Neves, Pedro Leão
Abstract : The increased level of plasma total homocysteine (tHcy) in chronic kidney disease patients has been reported as a new and independent risk factor for cardiovascular disease. However, after the description of reverse epidemiology in the renal population, the association of tHcy and nutrition became less clear. We evaluated the association between homocysteine, nutritional status, and inflammation, and their impact on mortality in 95 predialysis patients. High sensitivity C-Reactive Protein (hs-CRP), interleukin 6 (IL-6), Tumor Necrosis Factorα (TNF-α )], and tHcy were evaluated, as was the nutritional status by the modified Subjective Global Nutritional Assessment (mSGA). We divided our population in four groups according to their tHcy and mSGA values being above or below the mean level and found the lowest survival in the group with tHcy and mSGA above the mean level, as well as higher levels of IL-6 (P = .03 ) and TNF-α (P = .045 ). Higher levels of homocysteine can be associated with higher mortality in predialysis patients, as long as they are associated with malnutrition and inflammation.